2021
DOI: 10.3389/fphys.2021.632058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exposure at Different Altitudes on the Executive Function of Plateau Soldiers—Evidence From ERPs and Neural Oscillations

Abstract: This study investigates the changes in soldiers' brain executive function at different altitude environments and their relationship with blood oxygen saturation. Stratified sampling was conducted in different altitude 133 active-duty soldiers who were stationed in Weinan (347 m, n = 34), Nyingchi (2,950 m, n = 32), Lhasa (3,860 m, n = 33), and Nagqu (4,890 m, n = 34) for 2 years. The Go/NoGo paradigm with event-related potentials (ERPs) and event-related oscillations (EROs) was used to explore the time and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Headache (1) and transient cerebral ischemia (2) were also common neurological symptoms associated with HA. And the reasons why individuals from low to high altitudes can develop sleep-disordered breathing (SDB) involved not only the stimulation of peripheral chemoreceptors of the carotid body which adjust the frequency and depth of breathing by detecting changes in arterial O 2 -7 and CO 2 -pH but also the instability of feedback control system resulting from the high gain in the system and changes in the ventilatory recruitment threshold (3,4). In severe cases, people can develop mountain sickness, high-altitude cerebral edema, Abbreviations: stage 1, plain; stage 2, in the 3rd month at an altitude of 1,650 m; stage 3, in the 3rd month at an altitude of 4,000 m; stage 4, in the 9th month at an altitude of 4,000 m; AHI, apnea-hypopnea index; TST, total sleep time; TSA90, the duration of time with SaO 2 < 90%; LAT, the longest apnea time; MAT, the mean apnea time; MSpO 2 , the mean pulse oxygen saturation; LSpO 2 , the lowest pulse oxygen saturation; SpO 2 , pulse oxygen saturation; NM, negative mood; PM, positive mood; TMD, total mood disturbance; F+B score, forward+backward score; SAS, sleep apnea; OSA, obstructive sleep apnea syndrome; CSA, central sleep apnea.…”
Section: Introductionmentioning
confidence: 99%
“…Headache (1) and transient cerebral ischemia (2) were also common neurological symptoms associated with HA. And the reasons why individuals from low to high altitudes can develop sleep-disordered breathing (SDB) involved not only the stimulation of peripheral chemoreceptors of the carotid body which adjust the frequency and depth of breathing by detecting changes in arterial O 2 -7 and CO 2 -pH but also the instability of feedback control system resulting from the high gain in the system and changes in the ventilatory recruitment threshold (3,4). In severe cases, people can develop mountain sickness, high-altitude cerebral edema, Abbreviations: stage 1, plain; stage 2, in the 3rd month at an altitude of 1,650 m; stage 3, in the 3rd month at an altitude of 4,000 m; stage 4, in the 9th month at an altitude of 4,000 m; AHI, apnea-hypopnea index; TST, total sleep time; TSA90, the duration of time with SaO 2 < 90%; LAT, the longest apnea time; MAT, the mean apnea time; MSpO 2 , the mean pulse oxygen saturation; LSpO 2 , the lowest pulse oxygen saturation; SpO 2 , pulse oxygen saturation; NM, negative mood; PM, positive mood; TMD, total mood disturbance; F+B score, forward+backward score; SAS, sleep apnea; OSA, obstructive sleep apnea syndrome; CSA, central sleep apnea.…”
Section: Introductionmentioning
confidence: 99%
“…This is one of the important reasons for the decreased clearance of sildenafil in rats after acute hypoxia, i.e ., changes in biochemical indicators mainly affect the distribution, clearance, and excretion of sildenafil. Several studies have shown that high-altitude environments have varying degrees of impact on human physiological functions and their circadian rhythms, brain functions, and behavioral functions ( Ma, 1988 ; Rostrup et al, 2005 ; Xie et al, 2020 ; Wei et al, 2021 ). Therefore, it is expected that similar results may be observed in humans in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with a previous study that showed that acute exposure to 2600 m altitude (simulated normobaric hypoxia) did not impair spatial working memory [ 15 ]. Moreover, another study on long-term exposure to moderate altitude showed that two years of exposure to 2950 m altitude did not affect response inhibition [ 19 ]. Our findings provide further evidence that there is no detectable influence of long-term exposure to moderate altitude on spatial working memory performance, whereas a study on high altitude showed that long-term (three years) exposure to 3650 m altitude decreased spatial working memory performance [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous behavioral study showed that no significant changes were found in most cognitive functions (including new verbal learning and memory, working memory, long-term explicit memory, implicit procedural learning and short- and long-term visual memory) after six months of exposure to 2260 m altitude, except for visual perception [ 18 ]. In addition, a recent study using the Go/NoGo paradigm with event-related potential (ERP) showed that no changes were found in behavioral performance, while the amplitude of P3 was significantly decreased after two years of exposure to 2950 m [ 19 ]. Adaptation based on compensatory mechanisms may account for the preserved cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation